Administrative Impropriety Law and the mandatory protection of the public manager in the implementation of public policies guaranteeing fundamental rights under the neo constitutionalism view (International Journal of Geoscience, Engineering and Technology, 2022)
Through bibliographical, documental, and jurisprudential research of applied nature, the present study aims to prove the public manager's framing in the Administrative Misconduct Law, in his eventual denial of the realization of the fundamental rights foreseen in the Federal Constitution through public policies. The problem is the lack of discretion of the Public Manager in implementing measures to protect citizens from fundamental guarantees, which, otherwise, would offend both constitutional and public administration principles, such as efficiency, legality, and morality. Therefore, the constitutional character of the LIA is explained, as well as the sanctions provided for in its text, to prove that such omissions are considered acts of administrative improbity. Through jurisprudential research on the website of the Federal Supreme Court (STF), it is recognized, however, the absence of accountability in the omission of public policy implementation by the Public Manager, even though it is considered the negative in different typification’s. It concludes, showing the Public Manager as a protagonist in the implementation of public policies, a true guardian of the citizen before a true Democratic State of Law.